Ethnomathematics exploration on tourism in the rice field of pematang johar as a mathematics lesson - Paramita, Sintia; Asrul, Asrul (Desimal: Jurnal Matematika, 2023)
This research aims to find out, examine, and describe what are the elements of applying mathematics, as well as explore the mathematical concepts that exist in the Spatial Planning of Taman Sawah Tourism in Pematang Johar Village. This research took place in Pematang Johar Village, Labuhan Deli District, Deli Serdang, North Sumatra. The type of research that the author examined was descriptive qualitative research, in which the collection of data was taken through a process of documentation, direct observation, and literature review. The documentation and observation are used to explore ethnomathematics and mathematical concepts in the Taman Sawah Tourism in Pematang Johar Village, while literature review is used to find out about the cultural values that exist in the Sawah Park Tourism in Pematang Johar Village. Based on the results of data collection, several mathematical concepts were obtained in the rice field garden tour, namely (1) Flat Shape Concept, (2) Line Concept, (3) Geometry Transformation Concept, (4) Set Concept. These tourist attractions can be used as a medium for learning mathematics, especially at the elementary and secondary levels, in order to increase interest in learning mathematics.